2014
DOI: 10.1039/c3ee43619e
|View full text |Cite
|
Sign up to set email alerts
|

Flexible high efficiency perovskite solar cells

Abstract: Flexible perovskite based solar cells with power conversion efficiencies of 7% have been prepared on PET based conductive substrates. Extended bending of the devices does not deteriorate their performance demonstrating their suitability for roll to roll processing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
288
2
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(301 citation statements)
references
References 25 publications
5
288
2
6
Order By: Relevance
“…The process is also compatible with flexible device applications, as demonstrated by Bolink and cow-orkers, who showed the remarkable mechanical properties of sublimed perovskite films in flexible devices. [72,73] An initial setback to the process is that the perovskite crystallization during evaporation seems to be affected by the choice of substrate. In particular, MAI seems to have a varying affinity to physisorb on certain substrates and might even decompose, which hinders the formation of the perovskite phase in the first few nanometers.…”
Section: Alternatives To Solution-processed Thin Filmsmentioning
confidence: 99%
“…The process is also compatible with flexible device applications, as demonstrated by Bolink and cow-orkers, who showed the remarkable mechanical properties of sublimed perovskite films in flexible devices. [72,73] An initial setback to the process is that the perovskite crystallization during evaporation seems to be affected by the choice of substrate. In particular, MAI seems to have a varying affinity to physisorb on certain substrates and might even decompose, which hinders the formation of the perovskite phase in the first few nanometers.…”
Section: Alternatives To Solution-processed Thin Filmsmentioning
confidence: 99%
“…Since the¯rst reports, 6,7 the solid state perovskite solar cell has been developed very fast to reach a power conversion e±ciency (PCE) above 15%. 8,9 Several studies have reported on solar cell structure, 7,[10][11][12] alternative organic materials, [13][14][15] charge transport mechanism, [16][17][18] perovskite preparing methods, 8,19,20°e xible solar cell, [21][22][23] and modules. 24 Although perovskite solar cell can also work without hole transport material (HTM), with a PCE of 5-8%, 12,25 transient absorption results show that the most e±cient charge separation is obtained when using TiO 2 and HTM together.…”
Section: Introductionmentioning
confidence: 99%
“…This lowtemperature processability enables the manufacture of solar cells on flexible substrates in large scale. 23,24 In addition, the inverted planar heterojunction structured perovskite devices show better stability under ultraviolet light than the mesoporous structured devices. 25 Subsequently, extensive work has been carried out on the planar heterojunction structured perovskite device, which pushes the device PCEs higher and higher, 16,26,27 including progressive effort on optimizing the crystallization process and morphology tuning of the perovskite films.…”
mentioning
confidence: 99%